LABA BERSIH DAN KEBIJAKAN HUTANG SERTA DAMPAKNYA TERHADAP KEBIJAKAN DEVIDEN - Sopiati, Sopi; Novianti, Windi (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2018)
This research was conducted in Property and Real Estate companies listed on the Indonesian Stock Exchange (IDX). The purpose of this study is to develop how much influence the net income and debt policy, as measured by debt to equity ratio (DER) partially and simultaneously on dividend policy as measured by the dividend payout ratio (DPR). The method used in this research is descriptive method verification with quantitative approach. The sample used in this study is the annual financial statements 2010 - 2014 as many as 30 samples. The test statistic used is multiple linear regression analysis, the classical assumption test, analysis of the correlation coefficient, determination coefficient and hypothesis testing using SPSS V.20.00 for windows. Results of the analysis showed that the net income positive effect on dividend policy (DPR), debt policy (DER) a negative effect on dividend policy (DPR), net income and debt policy (DER) and simultaneous partial effect on dividend policy (DPR). Keywords : net income, debt policy, dividend policy